2010
DOI: 10.1103/physrevb.81.144508
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of the Campbell regime in superconducting stripes

Abstract: A combination of scanning Hall microscopy and scanning ac-susceptibility measurements in superconducting stripes ͑ribbons͒ of width w Ͻ 10 m was used to observe the dimensional phase transitions of the vortex lattice and its stability under alternating fields. At low dc magnetic fields applied perpendicularly to the plane of the stripes, vortices form a one-dimensional chain at the center of the stripes. Above a certain field H ‫ء‬ ͑w͒, the vortex chain splits in two parallel rows displaced laterally in such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…For instance, for one single vortex-antivortex pair, the high degeneracy in the position of the antivortex makes it more susceptible to small excitation forces than the vortex pinned by the disk. This hypothesis can be experimentally demonstrated by using a scanning ac-susceptibility technique, which reveals the points of maximum amplitude of oscillation of each individual vortex when submitted to an external ac field [30]. In Fig.…”
Section: Different Vortex and Antivortex Mobilitymentioning
confidence: 89%
“…For instance, for one single vortex-antivortex pair, the high degeneracy in the position of the antivortex makes it more susceptible to small excitation forces than the vortex pinned by the disk. This hypothesis can be experimentally demonstrated by using a scanning ac-susceptibility technique, which reveals the points of maximum amplitude of oscillation of each individual vortex when submitted to an external ac field [30]. In Fig.…”
Section: Different Vortex and Antivortex Mobilitymentioning
confidence: 89%
“…In previous works [26][27][28], we have demonstrated that the SSM technique is capable of extracting useful information of individual vortex dynamics with single-vortex resolution. Here we benefit from the MD simulation to analyze the vortex trajectories at much smaller scales.…”
Section: Trajectories Of a Single Vortexmentioning
confidence: 98%
“…The incapacity to resolve the ac-response of a single vortex and the indirect relation between the vortex dynamics and the integrated response can be circumvented by the scanning ac-susceptibility microscopy (SSM) technique, [6][7][8] which allows to probe the in-and out-of-phase response to an applied ac magnetic field or current with single-vortex resolution. 3,8,9 In contrast to standard susceptibility measurements, in SSM the periodic change in flux due to vortex motion and screening currents is measured locally by scanning a submicron-sized Hall probe over the surface, thereby revealing the microscopic vortex response.…”
Section: And References Therein)mentioning
confidence: 99%
“…3,8,9 In contrast to standard susceptibility measurements, in SSM the periodic change in flux due to vortex motion and screening currents is measured locally by scanning a submicron-sized Hall probe over the surface, thereby revealing the microscopic vortex response. Moreover, the screening current response imaged close to the border, also probed in classical macroscopic ac-susceptibility experiments, can be cross-correlated with the present vortex physics and the theoretical models describing them.…”
Section: And References Therein)mentioning
confidence: 99%
See 1 more Smart Citation